Forest Structure, Wood Standing Stock, and Tree Biomass in Different Restoration Systems in the Brazilian Atlantic Forest - Fideles Pontes, Danila Morena [UNESP]; Engel, Vera Lex [UNESP]; Parrotta, John A. (Mdpi, 2019)
Reliable estimates of tree growth and wood yield are fundamental to support the management of restored forests and better reconcile the objectives of recovering biodiversity with the provision of ecosystem services. In this study, wood standing volumes and tree biomass stocks were estimated in different ecological restoration systems and at two sites with contrasting soil fertility, in order to evaluate the potential trade-offs between biodiversity and forest production. At each site, a complete randomized block design, with three replications of six treatments, was established in 1997-1998: direct seeding (DIRS), high-diversity tree plantation (HDIV), modified Taungya agroforestry system (AFS), mixed plantation with timber and firewood species (MIX), managed agroforestry system (AFSm) and managed mixed plantation (MIXm). We inventoried all trees with diameter at breast height (DBH) >= 5 cm in 450 m(2) per treatment per plot, 19-20 years after establishment, using site-specific allometric models. Significant site effects were found for tree height, tree density and wood volume. Restoration systems (treatments) affected forest structure and forest productivity. Higher wood stock and biomass tree were observed in the less complex system (DIRS), while AFSm and HDIV reconciled higher species richness and diversity with good wood volume yields and tree biomass.
Keywords: tropical semideciduous seasonal forest; ecological restoration; agroforestry; ecosystem services; Legal Reserve